The lost scientists of World War II - Clary, David C. (World scientific, 2024)
"The Lost Scientists of World War II tells the stories of scientists from Germany and other European countries who vanished during World War II. These erudite scholars contributed to diverse scientific fields and were associated with some of the world's leading universities and research institutions. Despite their proficiency, they all sought help from agencies to relocate to the UK in the 1930s, but were unable to secure the necessary assistance. This book highlights the extraordinary narratives of thirty such scientific refugees, delving into the reasons behind the unavailability of aid and presenting fresh insights into the tragic fates or astounding survival experiences of these individuals"